LabVIEW-Based Control of a Switching Board for Distance E-Learning - Adrian Popovici; Viorel Popescu; Mihaela Lascu; Mircea Băbăiţă; Dan Lascu; Dan Negoiţescu (Journal of Electrical and Electronics Engineering, 2008)
The paper presents hardware and softwareaspects regarding design and LabVIEW control of aswitching board interface used in distance learning.Finally a relay matrix is controlled according to a desired32-bit word sequence. This is intended in studying powerelectronics and the authors used it in practicalconfiguring and experimenting different types ofuncontrolled rectifiers.